Chemical Phase Separation of Superconductive and Ferromagnetic Domains in ZnNNi3−xCox. (31st December 2012) - Yamazaki, Takahiro; Uehara, Akira; Kozawa, Katsuya; Kimisima, Yoshihide; Uehara, Masatomo
Abstract : Various ZnN y Ni3− x Co x compounds with differing Co content, x, were synthesized, and their magnetic properties were investigated. Uniform solid solutions could not be obtained at low Co content (x < 0.75 ); instead micrometer-scaled ferromagnetic ZnN y Ni0.6 Co2.4 domains formed embedded within a superconductive ZnNNi3 bulk, showing chemical phase separation of superconductive ZnNNi3 and ferromagnetic ZnN y Ni0.6 Co2.4 . At intermediate levels of Co concentration (0.75 < x < 2 ), this two-phase separation might persist, and the superconductive behavior was strongly suppressed in this composition region. Only at high Co concentration (x > 2 ) the uniform ferromagnetic solid solution ZnN y Ni3− x Co x (with most likely y = 0.5 ) formed. The phase separation behavior is intrinsic to the system, reflecting the existence of a miscibility gap in ZnN y Ni3− x Co x for the samples with x < 2, and was shown not to be attributable to incomplete synthesis. In the two-phased samples, high-quality granular contact between the superconductor and ferromagnet has been realized, suggesting that the production of useful devices requiring high-quality contacts between superconductors and ferromagnets may be possible by making use of this two-phase situation.